Sexual and asexual reproduction in the colonial ascidian Botryllus schlosseri. Issue 1 (23rd July 2014) - Gasparini, Fabio; Manni, Lucia; Cima, Francesca; Zaniolo, Giovanna; Burighel, Paolo; Caicci, Federico; Franchi, Nicola; Schiavon, Filippo; Rigon, Francesca; Campagna, Davide; Ballarin, Loriano; Christiaen, Lionel; et al.
Summary The colonial tunicate Botryllus schlosseri is a widespread filter‐feeding ascidian that lives in shallow waters and is easily reared in aquaria. Its peculiar blastogenetic cycle, characterized by the presence of three blastogenetic generations (filtering adults, buds, and budlets) and by recurrent generation changes, has resulted in over 60 years of studies aimed at understanding how sexual and asexual reproduction are coordinated and regulated in the colony. The possibility of using different methodological approaches, from classical genetics to cell transplantation, contributed to the development of this species as a valuable model organism for the study of a variety of biological processes. Here, we review the main studies detailing rearing, staging methods, reproduction and colony growth of this species, emphasizing the asymmetry in sexual and asexual reproduction potential, sexual reproduction in the field and the laboratory, and self‐ and cross‐fertilization. These data, opportunely matched with recent tanscriptomic and genomic outcomes, can give a valuable help to the elucidation of some important steps in chordate evolution. genesis 53:105–120, 2015. © 2014 Wiley Periodicals, Inc.